Shooting method with sign-changing nonlinearity. (February 2015) - Cheng, Ze; Li, Congming
Abstract: In this paper, we study the existence of solution to a nonlinear system: (0.1) − Δ u i = f i ( u ) in R n, u i > 0 in R n